-4=-7(2x+1)+6x+3(3x+1)

Simple and best practice solution for -4=-7(2x+1)+6x+3(3x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4=-7(2x+1)+6x+3(3x+1) equation:



-4=-7(2x+1)+6x+3(3x+1)
We move all terms to the left:
-4-(-7(2x+1)+6x+3(3x+1))=0
We calculate terms in parentheses: -(-7(2x+1)+6x+3(3x+1)), so:
-7(2x+1)+6x+3(3x+1)
We add all the numbers together, and all the variables
6x-7(2x+1)+3(3x+1)
We multiply parentheses
6x-14x+9x-7+3
We add all the numbers together, and all the variables
x-4
Back to the equation:
-(x-4)
We get rid of parentheses
-x+4-4=0
We add all the numbers together, and all the variables
-x=0
x=0/-1
x=0

See similar equations:

| 9x-(5x-12)=39 | | 4=3x=10 | | 2/3y+1/3=1/3y+2/3 | | 4/3+1/2t=7 | | m=5(4+m)2 | | -2+4=x+16 | | x+2(x+6)=222 | | 4/5s+7=495 | | 6x-1=3x+6 | | 10x-3=2(5x-1) | | 7x=4-15x=-19 | | 6=-2/7+b | | 45x=25x+129 | | x²-12x=20 | | 150m-100m+42,750=46,125-175m | | 1/3=4/3x-1 | | 3(x+2)-5=x-3 | | 4(x-4)+x=104 | | 72x-17=-89 | | 2p^2+5p+1=0 | | 15+4x-3x=0 | | 3x-3=1-(2x-4) | | 8(v-3)=2v+18 | | |8n=2|+17=10 | | 3/2x-4=21 | | 18–-16h=-894 | | 3r–9=4r | | x=12+8x-8x-3(x+4)-4x | | -8v+5v=9 | | 6x-10=1+5x | | 7=y+1 | | 3x-9+8x-24=6x-24+16x+8 |

Equations solver categories